(untitled) (Medical Forum Monthly, 2020)
Objective: The aim of this study was to identify frequency of early symptomatic DIC in neonates presenting with sepsis resulting in major neonatal morbidity and mortality. Study Design: It was a cross-sectional study. Place and Duration of Study: This study was conducted at the Pediatric department, Fatima Memorial Hospital, Lahore from July 2016 to January 2017. Materials and Methods: A total of 200 patients were included in this study. Venous sample 3cc was collected to get CBC, CRP, blood culture and sensitivity, PT, APTT, FDP’s, CXR, urine R/E and culture and sensitivity, LP when required. All the data was analyzed using SPSS version 20. Results: The mean gestational age of the patients was 38.76 ± 1.19 weeks. The mean duration of symptoms was found as 13.25 ± 3.29 days. There were 111 (55.5%) males and 89 (45.5%) females in our study. DIC was found in 85 patients (42.5%) while not found in 115 patients (57.5%). DIC was also stratified according to gestational age, gender and duration of symptoms and was found significant for gestational age and duration of symptoms. Conclusion: A high percentage of DIC (42.5%) was found in patients presenting with neonatal sepsis.